2016
DOI: 10.1186/s12877-016-0328-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the prevalence and variance of cognitive impairment, pain, neuropsychiatric symptoms and ADL dependency among persons living in nursing homes; a cross-sectional study

Abstract: BackgroundEarlier studies in nursing homes show a high prevalence of cognitive impairment, dependency in activities of daily living (ADL), pain, and neuropsychiatric symptoms among residents. The aim of this study was to explore the prevalence of the above among residents in a nationally representative sample of Swedish nursing homes, and to investigate whether pain and neuropsychiatric symptoms differ in relation to gender, cognitive function, ADL-capacity, type of nursing-home unit and length of stay.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 46 publications
(65 reference statements)
6
109
1
4
Order By: Relevance
“…The remaining (42%) of the assessments were completed by a staff member knowing the resident ‘well’ by interacting with the resident weekly (Björk et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The remaining (42%) of the assessments were completed by a staff member knowing the resident ‘well’ by interacting with the resident weekly (Björk et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Malnutrition remains a clinical priority in 20%–66.5% institutionalised older people (Namasivayam & Steele, ; Papparotto, Bidoli, & Palese, ). In nursing homes, older dysphagic patients often suffer from cognitive impairment (Björk et al., ) and are also more at risk of malnutrition and sarcopaenia. The risk of malnutrition increases in relation to the presence of cognitive impairment (OR: 1.844; p = .001), dementia (OR: 2.139; p = .001), but also in relation to the mere condition of dependency during meals (OR: 2.257; p = .001; Moreira et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that a large proportion of nursing home residents, and almost two‐thirds of the sample in this study, are recognized as potentially having some form of cognitive impairment, it seemed important to first examine the feasibility of the TOPAS for proxy‐rated use in this population (Björk et al, ; Björk, Lövheim, et al, ). Previous testing of the 32‐item TOPAS suggested that the scale produced reliable proxy ratings when comparing mentally lucid residents’ self‐ratings, staff proxy ratings and relative proxy ratings (Bergland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing home staff provided demographic information for residents and answered survey questions as proxy raters regarding cognitive status, activity function and thriving (Edvardsson et al, ). Proxy ratings were used based on the suspected, and later confirmed, high prevalence of cognitive impairment among Swedish nursing home residents (Björk et al, ). No identifying information was collected for residents or staff.…”
Section: The Studymentioning
confidence: 99%